Trajectory of pulmonary function parameters and radiology progress among patients with Idiopathic pulmonary fibrosis treated with Doxycycline - Heraganahally, Subash S; Howarth, Timothy; Garg, Himanshu (Nepalese Respiratory Journal, 2022)
Idiopathic pulmonary fibrosis is the most common and lethal form of interstitial lung diseases, with an associated median survival of only 2 to 3 years. Doxycycline through its matrix metalloproteinase inhibition property may be useful in slowing the disease progression among patients with ILD. However, there are only anecdotal reports in the literature in demonstrating long term trajectory in lung function parameters and radiology progress among IPF patients treated with doxycycline. In this report we describe the clinical course of two patients with IPF treated with doxycycline. We also compared the decline in the pulmonary function parameters in our patients with previously published predicted values for normal ageing (non-IPF), placebo, nintedanib and pirfenidone treated patients.